Wrinkle recovery angle enhancement and tensile strength loss of 1, 2, 3, 4-butanetetracarboxylic acid finished lyocell fabrics. Issue 17 (September 2020) - Ke, Guizhen; Xiao, Zhiheng; Jin, Xinya; Yu, Lixiang; Li, Jianqiang; Zhang, Huixia
The formaldehyde-free crease-proof finishing agent 1, 2, 3, 4, -butanetetracarboxylic acid (BTCA) was used to treat lyocell fabrics. The effects of BTCA concentration and curing temperature on the wrinkle recovery angle (WRA) and tensile breaking strength of lyocell fabrics were discussed. The results showed that with the increase of BTCA concentration and curing temperature, the WRA value of lyocell fabrics increased obviously and the maximum WRA reached 147°, but breaking strength decreased gradually and the minimum strength retention was 68%. The WRA was durable against laundering. The fabric whiteness difference was not obvious and the whiteness retention of all samples exceeded 98%. After further alkali treatment, the WRA of the treated lyocell fabrics decreased and the fracture strength retention recovered to varying degrees (0.45–10.8%). The developed regression equations were found to be in good correlation ( r 2 > 92%) with the selected variables (tensile strength, BTCA concentration, curing temperature). Fourier transform infrared spectroscopy analysis confirmed that the tensile strength loss of BTCA-treated lyocell fabrics was caused by cross-linking of cellulose molecules and acid degradation. Tensile strength loss that resulted from ester bonding could be restored after hydrolysis in alkaline solution. The recoverable magnitude of tensile strength was related to the curing temperature. A high temperature not only promoted the cross-linking of cellulose macromolecules, but also accelerated the acid degradation of cellulose.